Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA dengan Menggunakan Model Contextual Teaching and Learning pada Kelas V SDN Gebang 01 - Fahrizal Ananda Putra; Setia Hasanah Zuhdi; Azzahra’ Rahita Taufiq; Agung Setyawan (Journal on Education, 2023)
The effectiveness of a course of study is affected by the strategy used. When it comes to teaching science, a method that is oriented on the instructor is less successful. Belajar melalui Melakukan Konsep belajar mengajar dapat digunakan oleh pendidik dengan menempatkan siswa dalam konteks aktual di mana mereka dapat menerapkan pengetahuan kelas. Penelitian ini bertujuan untuk menyelidiki, "How effective are contextual learning methods in learning?" with specific reference to the sciences. Classroom action research (CAR) was used, and the study was written in a descriptive style to quickly describe the study's themes, sample procedures, data collecting methods, and data analysis procedures. This study's findings suggest there is room for improvement in the way science is taught to pupils. In Cycle I, students scored 64.46 on the understanding exam; in Cycle II, they scored 82.76, an increase of 38 percent. The "Contextual Teaching and Learning" technique has a success rate of 87%, indicating that it is effective in raising students' achievement in primary science.